Experiences at the centre of the world: meaning and monumentality at Delphi (c. 570-400 BCE) - Round, Charlotte Louise (2021)
In the ancient Greek mind, Delphi was the centre of the world, and it has been the focus of fascination and study for centuries. However, though we may have a wide array of textual and material evidence for the sanctuary, we still lack a full understanding of how it was experienced and understood by its ancient visitors. This is not a problem specific to Delphi: it is difficult to reconstruct experiences in most ancient sites given how few first-hand accounts survive from antiquity. The overarching question that this thesis will ask is, therefore, how visitors from around Greece would have seen, understood, and experienced Delphi, and how that experience contributed to social, political, cultural, religious and mythical identities. This thesis will examine the sanctuary of Apollo c. 570-400 BCE, corresponding to the period of Delphi’s greatest prestige.